Reliability of Eustachian tube function measurements in a hypobaric and hyperbaric pressure chamber. (14th May 2017) - Meyer, M.F.; Jansen, S.; Mordkovich, O.; Hüttenbrink, K.‐B.; Beutner, D.
Abstract : Objectives: Measurement of the Eustachian tube (ET) function is a challenge. The demand for a precise and meaningful diagnostic tool increases—especially because more and more operative therapies are being offered without objective evidence. The measurement of the ET function by continuous impedance recording in a pressure chamber is an established method, although the reliability of the measurements is still unclear. Methods: Twenty‐five participants (50 ears) were exposed to phases of compression and decompression in a hypo‐ and hyperbaric pressure chamber. The ET function reflecting parameters—ET opening pressure (ETOP), ET opening duration (ETOD) and ET opening frequency (ETOF)—were determined under exactly the same preconditions three times in a row. The intraclass correlation coefficient (ICC) and Bland and Altman plot were used to assess test‐retest reliability. Results: ICCs revealed a high correlation for ETOP and ETOF in phases of decompression (passive equalisation) as well as ETOD and ETOP in phases of compression (active induced equalisation). Very high correlation could be shown for ETOD in decompression and ETOF in compression phases. The Bland and Altman graphs could show that measurements provide results within a 95 % confidence interval in compression and decompression phases. Conclusions: We conclude that measurements in a pressure chamber are a very valuable tool in terms of estimating the ET opening and closing function. Measurements show some variance comparing participants, but provide reliable results within a 95 % confidence interval in retest. This study is the basis for enabling efficacy measurements of ET treatment modalities.